The clown of God : an old story - De Paola, Tomie (New York : Harcourt Brace, 1978)
A once-famous Italian juggler, now old and a beggar, gives one final performance before a statue of Our Lady and the Holy Child.
Notable/Best Books (A.L.A.)
School Library Journal
Book Links (A.L.A.)
3.1
K-3
Keywords: Jugglers and juggling -- Folklore; Folklore -- Italy; Folklore -- Italy; Juggling -- Folklore